Komunikasi Persuasif Duta Hijab: Penguatan Eksistensi Ajang Putri Hijab Bali - Baihaqi, Nabila; Permatasari, Ni Putu Intan (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
The existence of the Putri Hijab Bali pageant as a space for Muslim women’s empowerment is closely tied to the effectiveness of the persuasive communication carried out by the Hijab Ambassadors. In the multicultural society of Bali, the ability to convey messages appropriately becomes an essential factor in maintaining the pageant’s image and relevance. This study aims to analyze the persuasive communication strategies of the Hijab Ambassadors, the role of credibility in message delivery, and its impact on the social existence of the pageant. This research employs a descriptive qualitative approach through in-depth interviews, observations, and documentation. The findings indicate that the Hijab Ambassadors utilize a combination of central and peripheral persuasive routes by emphasizing message quality, visual branding, and digital interaction. Credibility, which includes expertise, trustworthiness, and behavioral consistency, proves to enhance audience acceptance of the messages delivered. The impact of persuasive communication is reflected in increased public awareness, strengthened positive imagery of Muslim women in Bali, and greater community participation in pageant activities. Thus, persuasive communication plays a significant role in maintaining the existence of the Putri Hijab Bali pageant through adaptive message strategies and effective use of digital media.